The teaching of the Bhagavad gita - Dayananda Swami (New Delhi Vision Books, 1988)
On the self (A?tman) as taught in Bhagavadgi?ta?.00
Includes passages in Sanskrit (Devanagari and roman)
Keywords: Criticism, interpretation, etc. 0.; B